La mediatización de las demandas de los contra-públicos subalternos - Barboza, Romina Andrea (Oficios Terrestres, 2015)
What happens when civil society organizations (women’s groups, environmental, lgbti), specifically, subaltern counterpublics or «weak public» (Fraser, 1997) channel their demands through the media? This article intends to elucidate through theoretical confrontation between several of the authors who think critically notions of public sphere, publics and public opinion. Considering the contributions of Jürgen Habermas, Nancy Fraser and Pierre Bourdieu this contains certain problems when if not contradictions. Nevertheless, the media visibility appears as a type of symbolic power that would allow them these actors to gain political representation and to alter, together with other actions, the relations of power established.